A stable inverse opal structure of cadmium chalcogenide for efficient water splitting1. Issue 36 (28th September 2015) - Lu, Yi-Ren; Yin, Peng-Fei; Mao, Jing; Ning, Meng-Jiao; Zhou, Yu-Zhu; Dong, Cun-Ku; Ling, Tao; Du, Xi-Wen
<x xml:space="preserve">Abstract</x> A highly conductive inverse opal structure consisting of cadmium chalcogenide nanocrystals achieves an unprecedentedly high hydrogen production rate, which originated from excellent light-absorption capacity and charge-separation efficiency.